Strategi Penanaman Nilai Kedermawanan Melalui Pembiasaan Makan Bersama - Iftitah, Selfi Lailiyatul; Prastyo, Danang; Hasanah, Wildatul; Irayana, Ika (JEA (Jurnal Edukasi AUD), 2024)
Early childhood is the future generation of the nation, positioned at a crucial stage of character, attitude, and mindset formation. However, in this modern era, many children exhibit disrespectful behavior and use foul language, which has become a serious concern for the education sector. One of the primary objectives of character education is to cultivate attitudes in children so they act by societal norms, characterized by affective traits such as values, attitudes, appreciation, and adaptability. One effective method for instilling character values is habituation, which enables children to internalize positive behaviors from an early age. This study aims to explore the process of instilling the value of generosity in early childhood through habituation during group meals. The research employs a descriptive qualitative approach, with primary data sources from the principal and teachers of RA As-Syahidul Kabir. Data were collected through observation, interviews, and documentation. The results of the study indicate that weekly group meals serve as an effective medium for fostering the value of generosity. In this activity, children bring food from home, but not all children come with food. This situation is utilized by teachers to encourage children to share their meals with peers who do not bring any. Additionally, children share side dishes, which vary among individuals, thereby strengthening the values of generosity and empathy. This act of sharing eventually becomes a positive habit ingrained in children through the group meal activity.